Teaching Expatriate Adaptation While Dealing With Reality: The Impact of a Tragedy on the Study-Abroad Experience - Levine, Kenneth J.; Levine, Sally L. (Journal of International Students, 2014)
This paper explores the relevance of the accepted U-shaped models of expatriate adaptation to students engaged in an international educational experience when they are faced with a tragedy. In this study-abroad course, an examination of the existing adaptation models and how they provide a set of expectations for the process of cultural adjustment is presented as course material. During a particular four-week summer program, one of the nineteen students who went abroad died in an accident at the end of the first week. It became clear after the tragedy that the models studied failed to explain the impact of a personal tragedy of this magnitude on the students’ adjustment process. This unfortunate event provided an opportunity to conduct a quasi-experiment to consider the impact of personal tragedy for students to question a body of research through their own personal experience and for scholars to re-examine and update the existing models.